2020
DOI: 10.1039/d0tc00391c
|View full text |Cite
|
Sign up to set email alerts
|

Tunable photoluminescence in Sb3+-doped zero-dimensional hybrid metal halides with intrinsic and extrinsic self-trapped excitons

Abstract: Dopants in luminescent metal halides provide an alternative way for photoluminescence tuning towards versatile optical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Next, introducing Sb 3+ as B-site dopant in organic-inorganic hybrid metal halides was studied. [43] The mixed matrix (C 9 NH 20 ) 9 [Pb 3 Cl 11 ](ZnCl 4 ) 2 is chosen as the host material due to its multiple inorganic ion sites as shown in Figure 7d (1-buty-1-methylpyrrolidinium), leading to a 0D structure. When Sb 3+ was introduced, Sb 3+ will replace Zn sites and the optical properties are discussed in Figure 7e,f.…”
Section: Photoluminescence Of Sb 3+ As Dopants With Long Wavelength Ementioning
confidence: 99%
See 3 more Smart Citations
“…Next, introducing Sb 3+ as B-site dopant in organic-inorganic hybrid metal halides was studied. [43] The mixed matrix (C 9 NH 20 ) 9 [Pb 3 Cl 11 ](ZnCl 4 ) 2 is chosen as the host material due to its multiple inorganic ion sites as shown in Figure 7d (1-buty-1-methylpyrrolidinium), leading to a 0D structure. When Sb 3+ was introduced, Sb 3+ will replace Zn sites and the optical properties are discussed in Figure 7e,f.…”
Section: Photoluminescence Of Sb 3+ As Dopants With Long Wavelength Ementioning
confidence: 99%
“…In our previous works, we found that Sb 3+ in low‐dimensional structures exhibited yellow–red‐color emissions. [ 15b,c,43 ] The crystal structure and optical properties of Cs 2 SnCl 6 :Sb 3+ is shown in Figure a–c. [ 15b ] Both singlet and triplet emission bands can be observed under high energy photoexcitation.…”
Section: The Luminescence Of Sb3+ In Metal Halidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast library of 0D Sb(III)‐halides allows the T q to be adjusted from below 200 K (iodides), to around RT (bromides), and above 400 K (chlorides). [ 45,52–70 ]…”
Section: Figurementioning
confidence: 99%